Pole piece, battery and electric equipment

By using a pole sheet with a double-layer active material layer structure in lithium-ion batteries, the particle size distribution and structure are optimized, and the problem of insufficient battery energy density and fast charging performance is solved, and the improvement of high energy density and fast charging performance is achieved.

CN119481365APending Publication Date: 2025-02-18BEIJING ELECTRIC VEHICLE
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411543794.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The energy density and fast charging performance of existing lithium-ion batteries are difficult to meet the high requirements of users.

Method used

The electrode sheet with a double-layer active material layer structure is optimized for the active material layer. Structure and composition to improve battery energy density and fast charging performance.

Benefits of technology

By optimizing the structure of the pole plate, the energy density and fast charging performance of the battery are improved, and the high-performance needs of users are met. At the same time, the capacity and circulation performance of the battery are improved without increasing manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481365A_ABST
    Figure CN119481365A_ABST
Patent Text Reader

Abstract

The invention discloses a pole piece, a battery and electric equipment, and relates to the technical field of batteries, at least one side of a current collector is provided with a first active material layer, and a second active material layer is arranged on the first active material layer; the first active material layer comprises a first type of active material, the second active material layer comprises a second type of active material, and the particle size distribution (D90-D10) / D50 of the first type of active material is greater than the particle size distribution (D90-D10) / D50 of the second type of active material. Therefore, the particle size distribution (D90-D10) / D50 of the first active substance is greater than the particle size distribution (D90-D10) / D50 of the second active substance, so that the second active substance with a smaller particle size in the second active substance layer is concentrated in distribution, small in tap density, small in filling density and high in porosity, Li < + > de-intercalation is facilitated, and the quick charging performance of the battery is improved; the first active substance with a large particle size in the first active substance layer can be widely distributed, the tap density is large, the filling density is large, and the energy density of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a pole piece, a battery and an electrical device. Background Art

[0002] Lithium-ion batteries have the advantages of high operating voltage, long cycle life and environmental protection. They are widely used in electric vehicles and other electrical equipment. However, with people's increasingly higher requirements for battery performance, the current battery energy density and fast charging performance are difficult to meet the user's requirements. Therefore, how to improve the battery energy density and fast charging performance has become a technical problem that needs to be solved urgently. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, one object of the present invention is to provide a pole piece that is conducive to improving the fast charging performance of the battery and the energy density of the battery.

[0004] The present invention further provides a battery having the pole piece.

[0005] The invention further provides an electrical device having the battery.

[0006] According to an embodiment of the present invention, the pole piece includes: a current collector, a first active material layer and a second active material layer. Along the thickness direction of the current collector, the first active material layer is provided on at least one side of the current collector, and the second active material layer is provided on the side of the first active material layer away from the current collector; the first active material layer includes: a first type of active material, the second active material layer includes: a second type of active material, and the particle size distribution (D90-D10) / D50 of the first type of active material is greater than the particle size distribution (D90-D10) / D50 of the second type of active material.

[0007] According to the pole piece of the embodiment of the present invention, by making the particle size distribution (D90-D10) / D50 of the first type of active material greater than the particle size distribution (D90-D10) / D50 of the second type of active material, the second type of active material with smaller particles in the second active material layer can be distributed in a concentrated manner, with a small tap density, a small filling density, and a high porosity, which is beneficial to Li+ deintercalation and extraction, and is beneficial to improving the fast charging performance of the battery. In addition, the first type of active material with larger particles in the first active material layer can be distributed widely, with a large tap density, and a large filling density, which is beneficial to improving the energy density of the battery.

[0008] In some examples of the present invention, the particle size distribution (D90-D10) / D50 of the first category active substance satisfies the relationship: 1≤(D90-D10) / D50≤1.2; the particle size distribution (D90-D10) / D50 of the second category active substance satisfies the relationship: 0.8≤(D90-D10) / D50≤1; and / or, the D90 of the first category active substance and the D90 of the second category active substance are both between 18μm and 25μm, the D50 of the first category active substance and the D50 of the second category active substance are both between 10μm and 15μm, and the D10 of the first category active substance and the D10 of the second category active substance are both between 6μm and 9μm.

[0009] In some examples of the present invention, the graphitization degree of the first type of active material is greater than the graphitization degree of the second type of active material.

[0010] In some examples of the present invention, the degree of graphitization of the first type of active material and the degree of graphitization of the second type of active material are both between 93% and 97%; and / or, the degree of graphitization of the first type of active material is between 95% and 97%, and the degree of graphitization of the second type of active material is between 93% and 95%.

[0011] In some examples of the present invention, the number of single particles in the first type of active substances accounts for greater than or equal to 50%, and the number of secondary particles in the second type of active substances accounts for greater than or equal to 70%.

[0012] In some examples of the present invention, the tap density of the first type of active material is greater than the tap density of the second type of active material.

[0013] In some examples of the present invention, the tap density of the first type of active material and the tap density of the second type of active material are both between 0.85 g / cm 3 ~1.4g / cm 3 and / or, the difference between the tap density of the first type of active material and the tap density of the second type of active material is A, satisfying the relationship: 0.05 g / cm 3 ≤A≤0.15g / cm 3 .

[0014] In some examples of the present invention, the first active material layer also includes: a first binder, a first dispersant and a first conductive agent, and the first type of active material, the first binder, the first dispersant and the first conductive agent satisfy a first mass ratio relationship: (95.3~97.3): (1.7~2.7): (0.7~1.3): (0.3~0.7); and / or, the second active material layer also includes: a second binder, a second dispersant and a second conductive agent, and the second type of active material, the second binder, the second dispersant and the second conductive agent satisfy a second mass ratio relationship: (96.1~98.17): (1.4~2.4): (0.2~0.8): (0.3~0.7); and / or, the first active material layer also includes: a first conductive agent, and the second active material layer also includes: a second conductive agent, and the content of the first conductive agent in the first active material layer is greater than the content of the second conductive agent in the second active material layer.

[0015] A battery according to an embodiment of the present invention includes an electrode assembly, which includes: a first pole piece, a second pole piece and a diaphragm, the first pole piece and / or the second pole piece are the above-mentioned pole pieces, and the first pole piece, the diaphragm and the second pole piece are assembled together to form the electrode assembly.

[0016] An electric device according to an embodiment of the present invention includes the above-mentioned battery.

[0017] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0019] Figure 1 Schematic diagram of a pole piece according to an embodiment of the present invention.

[0020] Reference numerals:

[0021] Pole piece 100;

[0022] Current collector 1; first active material layer 2; second active material layer 3. DETAILED DESCRIPTION

[0023] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0024] Reference below Figure 1 The electrode piece 100, a battery and an electric device according to an embodiment of the present invention are described.

[0025] like Figure 1 As shown, the pole piece 100 according to the embodiment of the present invention includes: a current collector 1 , a first active material layer 2 and a second active material layer 3 .

[0026] Among them, along the thickness direction of the pole piece 100 (ie Figure 1 The current collector 1, the first active material layer 2 and the second active material layer 3 are stacked. The current collector 1 can be copper foil, aluminum foil, composite current collector 1, etc. The current collector 1 can be used to collect and conduct current to ensure that the electrons in the battery or electrochemical device can flow smoothly. Figure 1 In the Z direction shown in the figure, a first active material layer 2 is provided on at least one side of the current collector 1, that is, a first active material layer 2 can be provided on one side of the current collector 1, or, first active material layers 2 can be provided on both sides of the current collector 1, and a second active material layer 3 is provided on the side of the first active material layer 2 facing away from the current collector 1.

[0027] The first active material layer 2 includes: a first type of active material, and the second active material layer 3 includes: a second type of active material. As some embodiments of the present application, both the first type of active material and the second type of active material may include at least one of graphite, silicon, hard carbon, soft carbon, silicon carbon, tin, lithium titanate, and mesophase carbon microspheres, wherein the graphite includes artificial graphite and / or natural graphite. For example: both the first type of active material and the second type of active material include graphite, silicon, and hard carbon, or both the first type of active material and the second type of active material include soft carbon, silicon carbon, tin, and lithium titanate, or both the first type of active material and the second type of active material include graphite, tin, and lithium titanate. The materials included in the first type of active material and the second type of active material can be selected according to the needs of the product to improve the selectivity of the first type of active material and the second type of active material, and by making the first type of active material and the second type of active material include a variety of materials, it is beneficial to improve the charge and discharge performance of the battery.

[0028] The particle size distribution (D90-D10) / D50 of the first type of active substance is greater than the particle size distribution (D90-D10) / D50 of the second type of active substance, where D90, D50 and D10 are the particle sizes of the active substances when the cumulative distribution of the number reaches 90%, 50% and 10%, respectively.

[0029] The present application is beneficial to improving the energy density and charge-discharge performance of the battery by providing a double-layer active material layer on at least one side of the current collector 1. In addition, the present application makes the particle size distribution (D90-D10) / D50 of the first type of active material greater than the particle size distribution (D90-D10) / D50 of the second type of active material, so that the second type of active material with a smaller particle size in the second active material layer 3 can be concentrated, the tap density and filling density of the second active material layer 3 can be small, and the porosity of the second active material layer 3 can be high, which is beneficial to Li+ deintercalation, and by making the particle size distribution (D90-D10) / D50 of the first type of active material greater than the particle size distribution (D90-D10) / D50 of the second type of active material, the first type of active material with a larger particle size in the first active material layer 2 can be distributed more widely, the tap density and filling density of the first active material layer 2 can be large, and the capacity of the battery can be improved. Moreover, such a setting can improve the capacity and fast charging performance of the battery without increasing the manufacturing cost.

[0030] Therefore, by making the particle size distribution (D90-D10) / D50 of the first type of active material greater than the particle size distribution (D90-D10) / D50 of the second type of active material, the second type of active material with smaller particles in the second active material layer 3 can be concentrated, with a small tap density, a small filling density, and a high porosity, which is beneficial to Li+ deintercalation and extraction, and is beneficial to improving the fast charging performance of the battery. In addition, the first type of active material with larger particles in the first active material layer 2 can be distributed more widely, with a large tap density and a large filling density, which is beneficial to improving the energy density of the battery.

[0031] As some embodiments of the present application, the pole piece 100 proposed in the present application may be a positive pole piece, and the pole piece 100 proposed in the present application may also be a negative pole piece. The present application is described by taking the pole piece 100 as a negative pole piece as an example.

[0032] In some embodiments of the present invention, the particle size distribution (D90-D10) / D50 of the first type of active material satisfies the relationship: 1≤(D90-D10) / D50≤1.2, that is, the particle size distribution (D90-D10) / D50 of the first type of active material can be any value between 1 and 1.2. For example, the particle size distribution (D90-D10) / D50 of the first type of active material can be but not limited to 1, 1.1, 1.2, etc. Such a setting can make the value of the particle size distribution (D90-D10) / D50 of the first type of active material reasonable, make the first type of active material with larger particle size in the first active material layer 2 distributed wider, make the first active material layer 2 have a large tap density and a large filling density, and can improve the capacity of the battery.

[0033] In some embodiments of the present invention, the particle size distribution (D90-D10) / D50 of the second type of active material satisfies the relationship: 0.8≤(D90-D10) / D50≤1, that is, the particle size distribution (D90-D10) / D50 of the second type of active material can be any value between 0.8 and 1. For example, the particle size distribution (D90-D10) / D50 of the second type of active material can be but not limited to 0.8, 0.9, 1, etc. Such a setting can make the second active material layer 3 have a small tap density and a small filling density, and can make the porosity of the second active material layer 3 higher, which is beneficial to Li+ deintercalation and extraction, and is beneficial to improving the fast charging performance of the battery.

[0034] In some embodiments of the present invention, the D90 of the first category active substance and the D90 of the second category active substance are both between 18 μm and 25 μm, the D50 of the first category active substance and the D50 of the second category active substance are both between 10 μm and 15 μm, and the D10 of the first category active substance and the D10 of the second category active substance are both between 6 μm and 9 μm.

[0035] That is to say, the D90 of the first category active substance and the D90 of the second category active substance can both be any value between 18μm and 25μm. For example, the D90 of the first category active substance and the D90 of the second category active substance can both be but are not limited to 18μm, 20μm, 22μm, 24μm, 25μm, etc.

[0036] The D50 of the first type of active substance and the D50 of the second type of active substance can both be any value between 10μm and 15μm. For example, the D50 of the first type of active substance and the D50 of the second type of active substance can both be but are not limited to 10μm, 12μm, 13μm, 14μm, 15μm, etc.

[0037] The D10 of the first type of active substance and the D10 of the second type of active substance can both be any value between 6 μm and 9 μm. For example, the D10 of the first type of active substance and the D10 of the second type of active substance can both be but are not limited to 6 μm, 7 μm, 8 μm, 9 μm, etc.

[0038] Such an arrangement can make the D90, D50, and D10 values ​​of the first and second active materials reasonable, and can also make the size relationship between the D90, D50, and D10 of the first and second active materials reasonable, which can improve the rate performance of the battery, and can take into account the processing performance and electrochemical performance of the electrode 100, which can improve the performance of the battery.

[0039] In some embodiments of the present invention, the degree of graphitization of the first type of active material is greater than the degree of graphitization of the second type of active material. It should be noted that the second type of active material has a lower degree of graphitization and a large interplanar spacing of the material, which is conducive to the entry and exit of active ions in the active material and reduces resistance. The first type of active material has a higher degree of graphitization, a high degree of ordering of the active material, fewer defects, and low surface activity. It is easy to form a stable and dense SEI film during the cycle, which is conducive to the improvement of cycle performance. Therefore, by making the degree of graphitization of the first type of active material greater than the degree of graphitization of the second type of active material, the relationship between the degree of graphitization of the first active material layer 2 and the second active material layer 3 can be made reasonable, which can not only improve the energy density of the battery, but also improve the fast charging performance of the battery.

[0040] In some embodiments of the present invention, the degree of graphitization of the first type of active material and the degree of graphitization of the second type of active material are both between 93% and 97%. In other words, the degree of graphitization of the first type of active material and the degree of graphitization of the second type of active material can both be any value between 93% and 97%. For example, the degree of graphitization of the first type of active material and the degree of graphitization of the second type of active material can both be but not limited to 93%, 95%, 97%, etc. Such an arrangement can make the degree of graphitization of the first type of active material and the degree of graphitization of the second type of active material reasonable, can reduce the defects inside the crystal, and is conducive to improving the energy density and fast charging performance of the battery.

[0041] In some embodiments of the present invention, the graphitization degree of the first type of active material is between 95% and 97%, and the graphitization degree of the second type of active material is between 93% and 95%.

[0042] That is to say, the degree of graphitization of the first type of active material can be any value between 95% and 97%. For example, the degree of graphitization of the first type of active material can be but not limited to 95%, 96%, 97%, etc. The degree of graphitization of the second type of active material can be any value between 93% and 95%. For example, the degree of graphitization of the second type of active material can be but not limited to 93%, 94%, 95%, etc. This setting can make the values ​​of the degree of graphitization of the first type of active material and the degree of graphitization of the second type of active material reasonable, and can also make the relationship between the degree of graphitization of the first type of active material and the degree of graphitization of the second type of active material reasonable, which can not only improve the energy density of the battery, but also improve the fast charging performance of the battery.

[0043] In some embodiments of the present invention, the number of single particles in the first category of active substances accounts for greater than or equal to 50%, and the number of secondary particles in the second category of active substances accounts for greater than or equal to 70%. It can be understood that the number of single particles in the first category of active substances accounts for greater than or equal to 50%, including the case where the number of single particles in the first category of active substances accounts for 100%, that is, pure single particles, and the number of secondary particles in the second category of active substances accounts for greater than or equal to 70%, including the case where the number of secondary particles in the second category of active substances accounts for 100%, that is, pure secondary particles.

[0044] By making the proportion of single particles in the first type of active material greater than or equal to 50%, the contact area between the first type of active material and the current collector 1 can be effectively increased, thereby improving the adhesion reliability of long-term multiple charge and discharge, and can improve the electron conduction efficiency, which is beneficial to improving the cycle performance and fast charging performance of the battery.

[0045] By making the proportion of secondary particles in the second type of active material greater than or equal to 70%, since the second active material layer 3 is closer to the diaphragm than the first active material layer 2 and the active ion concentration is higher, when the proportion of secondary particles in the second type of active material reaches a certain amount, the number of active ion channels that can be provided increases, which just matches the actual distribution of active ions in this area, which is beneficial to improving the battery's cycle performance and fast charging performance.

[0046] In some embodiments of the present invention, the tap density of the first type of active material is greater than the tap density of the second type of active material, that is, the tap density of the second type of active material is less than the tap density of the first type of active material. By making the tap density of the second type of active material relatively small, the second active material layer 3 can have a relatively high porosity and can adsorb and store more free electrolyte. By making the tap density of the first type of active material relatively large, it is beneficial to improve the energy density of the battery, thereby helping to increase the capacity of the battery.

[0047] In some embodiments of the present invention, the tap density of the first type of active material and the tap density of the second type of active material are both between 0.85 g / cm 3 ~1.4g / cm 3 That is to say, the tap density of the first type of active material and the tap density of the second type of active material can both be 0.85 g / cm 3 Up to 1.4g / cm 3 For example, the tap density of the first type of active material and the tap density of the second type of active material can be, but are not limited to, 0.85 g / cm 3 , 0.95g / cm 3 , 1.15g / cm 3 , 1.25g / cm3 , 1.4g / cm 3 Such a configuration can make the pole piece 100 have a high reversible capacity while also having good low cycle expansion performance and dynamic performance, thereby improving the energy density, fast charging performance and cycle performance of the battery.

[0048] In some embodiments of the present invention, the difference between the tap density of the first type of active material and the tap density of the second type of active material is A, which satisfies the relationship: 0.05 g / cm 3 ≤A≤0.15g / cm 3 Specifically, the tap density of the first type of active material is greater than the tap density of the second type of active material, and the difference A between the tap density of the first type of active material and the tap density of the second type of active material may be 0.05 g / cm 3 Up to 0.15g / cm 3 For example, the difference A between the tap density of the first type of active material and the tap density of the second type of active material may be, but is not limited to, 0.05 g / cm 3 , 0.10g / cm 3 , 0.15g / cm 3 Such an arrangement can make the tap density of the first type of active material and the tap density of the second type of active material change gradually, can form a gap gradient distribution, can improve the ion conductivity, and thus can improve the electrochemical performance of the electrode 100 .

[0049] In some embodiments of the present invention, the first active material layer 2 also includes: a first binder, a first dispersant and a first conductive agent, and the first type of active material, the first binder, the first dispersant, and the first conductive agent satisfy a first mass ratio relationship: (95.3~97.3): (1.7~2.7): (0.7~1.3): (0.3~0.7); and / or, the second active material layer 3 also includes: a second binder, a second dispersant and a second conductive agent, and the second type of active material, the second binder, the second dispersant, and the second conductive agent satisfy a second mass ratio relationship: (96.1~98.17): (1.4~2.4): (0.2~0.8): (0.3~0.7).

[0050] Among them, the first adhesive and the second adhesive may include: at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyethylene imine, polyaniline, lithium polyacrylate, sodium polyacrylate, polyacrylonitrile, polyacrylate, sodium alginate, styrene-butadiene rubber, phenolic resin, and epoxy resin. For example, the first adhesive and the second adhesive may both include polyvinylidene fluoride, polytetrafluoroethylene, and polyethylene imine. The first adhesive and the second adhesive may also include polyaniline, polyacrylic acid, and sodium alginate. In this way, the materials included in the first adhesive and the second adhesive can be selected according to product requirements, which is conducive to improving the selectivity of the first adhesive and the second adhesive. In addition, by making the first adhesive and the second adhesive include multiple materials at the same time, the bonding performance can be improved.

[0051] The first dispersant and the second dispersant may both include: lithium carboxymethyl cellulose and / or sodium carboxymethyl cellulose.

[0052] The first conductive agent and the second conductive agent may both include at least one of conductive carbon black, KS-6, acetylene black, Ketjen black, conductive fiber, graphene, conductive graphite, graphene oxide, and carbon nanotubes. For example, the first conductive agent and the second conductive agent may both include conductive carbon black, KS-6, and acetylene black. The first conductive agent and the second conductive agent may also include conductive carbon black, Ketjen black, conductive fiber, and graphene. The first conductive agent and the second conductive agent may also include acetylene black, conductive graphite, graphene oxide, and carbon nanotubes. In this way, the materials included in the first conductive agent and the second conductive agent may be selected according to product requirements, which is beneficial to improving the selectivity of the first conductive agent and the second conductive agent. In addition, by making the first conductive agent and the second conductive agent include multiple materials at the same time, the charge and discharge performance can be improved.

[0053] Taking the mass as 100, the mass ratio of the first type of active material, the first binder, the first dispersant, and the first conductive agent satisfies (95.3-97.3): (1.7-2.7): (0.7-1.3): (0.3-0.7). Such an arrangement can make the first mass ratio relationship reasonable, the proportion of each component in the first active material layer 2 reasonable, and the first active material layer 2 have excellent performance, which is beneficial to improving the fast charging performance and service life of the battery.

[0054] Taking the mass as 100, the mass ratio of the second type of active material, the second binder, the second dispersant, and the second conductive agent satisfies (96.1-98.17): (1.4-2.4): (0.2-0.8): (0.3-0.7). Such an arrangement can make the second mass ratio relationship reasonable, the proportion of each component in the second active material layer 3 reasonable, and the second active material layer 3 have excellent performance, which is beneficial to improving the fast charging performance and service life of the battery.

[0055] The first active material layer 2 also includes: a first conductive agent, and the second active material layer 3 also includes: a second conductive agent. The content of the first conductive agent in the first active material layer 2 is greater than the content of the second conductive agent in the second active material layer 3. Such a configuration is beneficial to improving the conductive performance of the electrode 100 and improving the fast charging performance of the battery.

[0056] The following is a comparison between the embodiments and the comparative examples. The lithium ion batteries of the embodiments 1-4 and the comparative examples 1-4 are all prepared according to the following method. Take the electrode sheet 100 proposed in the present application as a negative electrode sheet as an example.

[0057] 1) Preparation of positive electrode sheet: lithium cobalt oxide is used as the positive electrode active material, and then added into a stirring tank with conductive carbon black and polyvinylidene fluoride in a mass ratio of 97.2:1.5:1.3, and NMP solvent is added, and fully stirred according to the known batching process, and passed through a 200-mesh screen to prepare a positive electrode slurry, the solid content of which is 70% to 75%. The positive slurry is coated on an aluminum foil using a coating machine, and dried at 120°C to obtain a positive electrode sheet.

[0058] 2) Preparation of the first active material layer 2 slurry: 96.6wt% of the first type of active material, 0.6wt% of PAA, 1.3wt% of SBR, 0.5wt% of SP and 1wt% of CMC were prepared into a uniform slurry 1.

[0059] 3) Preparation of the slurry for the second active material layer 3: 97.2 wt% of the second type of active material, 1.4 wt% of PAA, 0.4 wt% of SBR, 0.5 wt% of SP and 0.5 wt% of CMC and water as a solubilizer are prepared into a uniform slurry 2.

[0060] 4) Negative electrode sheet partition coating: double-layer coating is used to complete a single-side coating, and the predetermined thickness of slurry 1 and slurry 2 is 40 μm;

[0061] 5) Preparation of lithium-ion batteries: The separator between the positive and negative electrodes is a composite separator of substrate + single-sided ceramic + double-sided adhesive. The winding machine is used to wind the core of the winding structure with the positive electrode wrapped outside. It is packaged with aluminum plastic film, baked under vacuum for 48 hours to remove moisture, and then the electrolyte is injected. The battery is then subjected to conventional formation and sorting to obtain a square soft-pack lithium-ion battery. The electrolyte is prepared using a conventional electrolyte formula: LiPF6 + solvent (EC + FEC + DEC + DMC + PS). The parameters are shown in the following table.

[0062]

[0063]

[0064] The testing process of lithium-ion batteries is shown in the following steps.

[0065] 1. Test methods

[0066] 1) Energy density

[0067] At an ambient temperature of 25°C±2°C, the lithium-ion battery is charged to an upper limit voltage at a 1 / 3C rate, and then discharged to a lower limit voltage at a 1 / 3C rate to obtain the energy during the discharge process of the lithium-ion battery.

[0068] The energy density of a lithium-ion battery (Wh / Kg) = the energy during the discharge of the lithium-ion battery / the mass of the lithium-ion battery.

[0069] 2) DC internal resistance

[0070] At 25℃±2℃ ambient temperature, charge at 1C constant current to the charge termination voltage and then switch to constant voltage charging. Stop charging when the charging current drops to 0.05I1 and let stand for 30min. Discharge at 0.33C current to SOC of 50%, let stand for 30min, and then discharge at 3.5C rate for 10s to obtain the DC internal resistance (DCR) of lithium-ion battery at 25℃ at 50% SOC.

[0071] 3) 1000 cycles capacity retention rate

[0072] In an environment of 25°C, the first charge and discharge are carried out. Constant current and constant voltage charging is performed at a charging current of 1.0C (i.e., the current value that completely discharges the theoretical capacity within 1 hour) until the upper limit voltage, and then constant current discharge is performed at a discharge current of 1.0C until the termination voltage, and the discharge capacity of the first cycle is recorded; then continuous charge and discharge cycles are performed.

[0073] Cycle capacity retention rate = (discharge capacity of the nth cycle / discharge capacity of the first cycle) × 10

[0074] 4) Lithium deposition rate

[0075] In an environment of 25°C, the charge and discharge test was carried out, and constant current discharge was carried out at a discharge current of 1.0C (the current value that completely discharges the theoretical capacity within one hour) until the termination voltage. Then, constant current charging was carried out at a charging current of 1.0C to the upper limit voltage, and constant voltage charging was continued until the current was 0.05C. At this time, the battery was fully charged. After the fully charged battery was allowed to stand for 5 minutes, constant current discharge was carried out at a discharge current of 1.0C to the termination voltage. The discharge capacity at this time was the actual capacity of the battery at 1.0C, recorded as C0. Then the battery was charged at a constant current of xC0 to the upper limit voltage, and then constant voltage charging was carried out to a current of 0.05C0. It was allowed to stand for 5 minutes, and the battery was disassembled to observe the lithium precipitation on the interface, and the charging rate was adjusted until lithium precipitation occurred, and the lithium precipitation rate was determined.

[0076] 2. Arrangement of temperature sensing line:

[0077] Temperature sensing wires must be attached during all tests. Unless otherwise specified, the temperature sensing wires are arranged in the center of the large surface, the positive terminal ear, and the negative terminal ear. Use high-temperature tape to attach the temperature sensing wires to avoid direct airflow.

[0078] The performance test results of Examples 1-4 and Comparative Examples 1-4 are shown in the following table.

[0079]

[0080] From the test results in the table, it can be seen that the negative electrode sheets of Examples 1-4 have low internal resistance, high capacity, high energy density, and good cycle performance, which can meet the battery energy density requirements and ensure the fast charging capability of the battery.

[0081] In Comparative Example 1, the negative electrode sheet has a single-layer structure, and the active material is artificial graphite with a particle size distribution of (D90-D10) / D50, a high tap density and a high degree of graphitization. Although this is beneficial to the embedding of lithium ions and is beneficial to improving the specific energy of lithium-ion batteries, the interlayer spacing d002 of the artificial graphite used in Comparative Example 1 is small, which may hinder the diffusion of lithium ions and cannot improve the kinetic performance of lithium-ion batteries.

[0082] In Comparative Example 2, the negative electrode sheet has a multi-layer structure, the first type of active material in the first active material layer 2 adopts artificial graphite with a particle size distribution of (D90-D10) / D50, a low tap density and a degree of graphitization, and the second type of active material in the second active material layer 3 adopts soft carbon with a particle size distribution of (D90-D10) / D50, a high tap density and a degree of graphitization. At this time, the specific energy of the lithium-ion battery is low, and the kinetic performance of the lithium-ion battery is also poor.

[0083] In Comparative Example 3, the negative electrode sheet has a multilayer structure, the first type of active material in the first active material layer 2 uses artificial graphite with a particle size distribution of (D90-D10) / D50, a low tap density and a low degree of graphitization, and the second type of active material in the second active material layer 3 uses intermediate phase microspheres with a particle size distribution of (D90-D10) / D50, a high tap density and a high degree of graphitization. At this time, the specific energy of the lithium ion battery is low, and the kinetic performance of the lithium ion battery is also poor.

[0084] In Comparative Example 4, the first type of active material in the first active material layer 2 uses natural graphite with a particle size distribution (D90-D10) / D50, a low tap density and a degree of graphitization, and the second type of active material in the second active material layer 3 uses artificial graphite with a particle size distribution (D90-D10) / D50, a high tap density and a degree of graphitization. At this time, the specific energy of the lithium-ion battery is low, and the kinetic performance of the lithium-ion battery is also poor.

[0085] By comparing Examples 1-4 with Comparative Examples 1-4, the electrode 100 provided by the present invention has low internal resistance, high capacity, high energy density, good cycle performance and safety performance. The present application can improve the energy density and fast charging performance of the battery by reasonably controlling the relative relationship between the particle size distribution (D90-D10) / D50 of the first type of active material and the particle size distribution (D90-D10) / D50 of the second type of active material.

[0086] In addition, the present application can make the pores of the second active material layer 3 large by reasonably controlling the particle size distribution (D90-D10) / D50 of the first type of active material, the tap density of the first type of active material, the graphitization degree of the first type of active material, the particle size distribution (D90-D10) / D50 of the second type of active material, the tap density of the second type of active material, and the graphitization degree of the second type of active material, so that the second active material layer 3 has excellent lithium ion transfer kinetics and good fast charging performance, and the first active material layer 2 can have high capacity and high compaction characteristics, which can not only meet the battery energy density requirements but also ensure the fast charging capability of the battery cell.

[0087] According to an embodiment of the present invention, the battery includes an electrode assembly, and the electrode assembly includes: a first electrode piece, a second electrode piece and a diaphragm. The first electrode piece and / or the second electrode piece is the above-mentioned electrode piece 100. The first electrode piece, the diaphragm and the second electrode piece are assembled together to form an electrode assembly. By making the particle size distribution (D90-D10) / D50 of the first type of active substance greater than the particle size distribution (D90-D10) / D50 of the second type of active substance, the second type of active substance with smaller particles in the second active substance layer 3 can be distributed in a concentrated manner, with a small tap density, a small filling density, and a high porosity, which is beneficial to Li+ deintercalation and deintercalation, and is beneficial to improving the fast charging performance of the battery. In addition, the first type of active substance with larger particles in the first active substance layer 2 can be distributed widely, with a large tap density and a large filling density, which is beneficial to improving the energy density of the battery.

[0088] According to the electrical equipment of the embodiment of the present invention, including the above-mentioned battery, by making the particle size distribution (D90-D10) / D50 of the first type of active material greater than the particle size distribution (D90-D10) / D50 of the second type of active material, the second type of active material with smaller particles in the second active material layer 3 can be distributed in a concentrated manner, with a small tap density, a small filling density, and a high porosity, which is beneficial to Li+ deintercalation and extraction, and is beneficial to improving the fast charging performance of the battery. In addition, the first type of active material with larger particles in the first active material layer 2 can be distributed widely, with a large tap density and a large filling density, which is beneficial to improving the energy density of the battery.

[0089] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0090] In the description of the present invention, "first feature" or "second feature" may include one or more of the features.

[0091] In the description of the present invention, "plurality" means two or more.

[0092] In the description of the present invention, a first feature being “on” or “under” a second feature may include that the first and second features are directly in contact with each other, or may include that the first and second features are not in direct contact with each other but are in contact with each other via another feature therebetween.

[0093] In the description of the present invention, “on”, “over” and “above” a first feature from a second feature includes the first feature being directly above and obliquely above the second feature, or simply means that the first feature is horizontally higher than the second feature.

[0094] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0095] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A pole piece (100), characterized in that: include: A current collector (1), a first active material layer (2) and a second active material layer (3), wherein along the thickness direction of the current collector (1), the first active material layer (2) is provided on at least one side of the current collector (1), and the second active material layer (3) is provided on a side of the first active material layer (2) facing away from the current collector (1); The first active material layer (2) comprises: a first type of active material, and the second active material layer (2) comprises: a second type of active material, and the particle size distribution (D90-D10) / D50 of the first type of active material is greater than the particle size distribution (D90-D10) / D50 of the second type of active material.

2. The pole piece (100) according to claim 1, characterized in that: The particle size distribution (D90-D10) / D50 of the first type of active substance satisfies the relationship: 1≤(D90-D10) / D50≤1.2; the particle size distribution (D90-D10) / D50 of the second type of active substance satisfies the relationship: 0.8≤(D90-D10) / D50≤1; And / or, the D90 of the first category active substance and the D90 of the second category active substance are both between 18μm and 25μm, the D50 of the first category active substance and the D50 of the second category active substance are both between 10μm and 15μm, and the D10 of the first category active substance and the D10 of the second category active substance are both between 6μm and 9μm.

3. The pole piece (100) according to claim 1, characterized in that: The graphitization degree of the first type of active material is greater than the graphitization degree of the second type of active material.

4. The pole piece (100) according to claim 1, characterized in that: The graphitization degree of the first type of active material and the graphitization degree of the second type of active material are both between 93% and 97%; And / or, the graphitization degree of the first type of active material is between 95% and 97%, and the graphitization degree of the second type of active material is between 93% and 95%.

5. The pole piece (100) according to claim 1, characterized in that: The number of single particles in the first type of active substances accounts for greater than or equal to 50%, and the number of secondary particles in the second type of active substances accounts for greater than or equal to 70%.

6. The pole piece (100) according to claim 1, characterized in that: The tap density of the first type of active material is greater than the tap density of the second type of active material.

7. The pole piece (100) according to claim 1, characterized in that: The tap density of the first type of active material and the tap density of the second type of active material are both between 0.85 g / cm 3 ~1.4g / cm 3 between; And / or, the difference between the tap density of the first type of active material and the tap density of the second type of active material is A, which satisfies the relationship: 0.05 g / cm 3 ≤A≤0.15g / cm 3 .

8. The pole piece (100) according to claim 1, characterized in that: The first active material layer (2) further comprises: a first binder, a first dispersant and a first conductive agent, wherein the first type of active material, the first binder, the first dispersant and the first conductive agent satisfy a first mass ratio relationship of: (95.3-97.3): (1.7-2.7): (0.7-1.3): (0.3-0.7); And / or, the second active material layer (3) further comprises: a second binder, a second dispersant and a second conductive agent, and the second type of active material, the second binder, the second dispersant and the second conductive agent satisfy a second mass ratio relationship: (96.1-98.17): (1.4-2.4): (0.2-0.8): (0.3-0.7); And / or, the first active material layer (2) further includes: a first conductive agent, and the second active material layer (3) further includes: a second conductive agent, and the content of the first conductive agent in the first active material layer (2) is greater than the content of the second conductive agent in the second active material layer (3).

9. A battery, characterized in that: The invention comprises an electrode assembly, wherein the electrode assembly comprises: a first pole piece (100), a second pole piece (100) and a diaphragm, wherein the first pole piece (100) and / or the second pole piece (100) is a pole piece (100) according to any one of claims 1 to 8, and the first pole piece (100), the diaphragm and the second pole piece (100) are assembled together to form the electrode assembly.

10. An electrical device, characterized in that: Comprising a battery according to claim 9.

Citation Information

Cited By

  • Secondary battery

    WO2026177202A1